Faktor-Faktor yang Memengaruhi Pelaksanaan Akuntansi Lingkungan (Studi pada KLH/BLH, Dinkeb, dan PDAM Kabupaten/Kota di Provinsi Jawa Tengah) - Taufiq Bagus Prasojo; Agus Purwanto (Diponegoro Journal of Accounting, 2013)
The objectives of this research is to analyze the influence of organization size, accounting regulation, and environmental management on environmental accounting practices. The samples used here are primary data from badan lingkungan hidup (BLH)/kantor lingkungan hidup (KLH), dinas kebersihan (Dinkeb), and perusahaan daerah air minum (PDAM) level regency. Data was collected by sent questionnaire directly to every responden. The sample collected were 17 KLH/BLH, 3 Dinkeb, and 13 PDAM.This research uses linear regression analysis to examine the hypothesis. Hypotheses examined by F test and t test. The results showed that organization size is not significant to influence environmental accounting practices, accounting regulation is significant positively to influence environmental accounting practices, and environmental management is not significant to influence environmental accounting practices.